2021
DOI: 10.1159/000514826
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Anxiety Level of Mothers of Children with Epilepsy during the COVID-19 Pandemic Period

Abstract: <b><i>Background and Aim:</i></b> Although anyone can be affected by the COVID-19 pandemic, it may cause additional concern for people with chronic conditions. Epilepsy is the most common neurological disease in childhood and adolescence. The aim of this study was to determine anxiety levels among the mothers of children under follow-up for epilepsy in our clinic during the COVID-19 pandemic. <b><i>Methods:</i></b> The study group consisted of the mothers of epil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 20 publications
(25 reference statements)
0
5
0
Order By: Relevance
“…In the study of Celik et al, mothers exhibited high levels of anxiety when their children had frequent seizures was significantly higher compared to mothers whose children have infrequent seizures, during the pandemic. However, no statistical difference was observed between mothers of CAWE who attended their appointment during the pandemic and those of the mothers who did not attend their follow-up appointment ( 27 ). On the contrary, a study in Sri Lanka showed low levels of stress among caregivers of CAWE during COVID-19 ( 11 ).…”
Section: Discussionmentioning
confidence: 90%
“…In the study of Celik et al, mothers exhibited high levels of anxiety when their children had frequent seizures was significantly higher compared to mothers whose children have infrequent seizures, during the pandemic. However, no statistical difference was observed between mothers of CAWE who attended their appointment during the pandemic and those of the mothers who did not attend their follow-up appointment ( 27 ). On the contrary, a study in Sri Lanka showed low levels of stress among caregivers of CAWE during COVID-19 ( 11 ).…”
Section: Discussionmentioning
confidence: 90%
“…This is consistent with the previous evidence that there was remarkable refraining from seeing a doctor during the pandemic [ 5 , 10 , 11 , 12 , 13 ]. Celik et al reported that parents of patients with epilepsy with a risk of unscheduled emergency visits were more anxious about COVID-19 infection associated with hospital visits than parents of patients without it [ 14 ]. Similarly, parents of patients with allergy may be more sensitive than those of healthy children due to the possibility of unscheduled emergency visits.…”
Section: Discussionmentioning
confidence: 99%
“…Full vaccination appeared to further reduce parental stress. [6,13] However, Kostopoulou et al, (2021) and Wauters et al, (2021) showed a positive correlation between the pandemic and parental stress, depressive symptoms and parental burnout. [18,19] Limitations of the study Throughout this study, several limitations appeared.…”
Section: Discussionmentioning
confidence: 99%